At-home genital nerve stimulation for individuals with SCI and neurogenic detrusor overactivity: A pilot feasibility study - Bourbeau, Dennis J. (J Spinal Cord Med, 2019)
Objective: Neurogenic bladder dysfunction, including neurogenic detrusor overactivity (NDO) is one of the most clinically significant problems for persons with spinal cord injury (SCI), affecting health and quality of life. Genital nerve stimulation (GNS) can acutely inhibit NDO-related reflex bladder contractions and increase bladder capacity. However, it is unknown if GNS can improve urinary continence or help meet individuals’ bladder management goals during sustained use, which is required for GNS to be clinically effective. Design: Subjects maintained voiding diaries during a one-month control period without stimulation, one month with at-home GNS, and one month after GNS. Urodynamics and quality of life assessments were conducted after each treatment period, and a satisfaction survey was taken at study completion. Setting: Subject screening and clinical procedures were conducted at the Louis Stokes Cleveland VA Medical Center. Stimulation use and voiding diary entries were conducted in subjects’ homes. Participants: Subjects included five men with SCI and NDO. Interventions: This study tested one month of at-home portable non-invasive GNS. Outcome Measures: The primary outcome measure was leakage events per day. Secondary outcome measures included self-reported subject satisfaction, bladder capacity, and stimulator use frequency. Results: GNS reduced the number of leakage events from 1.0 ± 0.5 to 0.1 ± 0.4 leaks per day in the four subjects who reported incontinence data. All study participants were satisfied that GNS met their bladder goals; wanted to continue using GNS; and would recommend it to others. Conclusions: Short term at-home GNS reduced urinary incontinence and helped subjects meet their bladder management goals. These data inform the design of a long-term clinical trial testing of GNS as an approach to reduce NDO.